The Effect and Safety Assessment of Metformin and DLBS3233 (A Bioactive Fraction of Lagerstroemia speciosa and Cinnamomum burmannii) on Improving Metabolic Parameters in Women with Polycystic Ovary Syndrome - Hidayat ST; Mulyantoro I; Damas S; Tjandrawinata RR (Dove Medical Press, 2023)
Syarief Thaufik Hidayat,1,2 Inu Mulyantoro,1,2 Suhartono Damas,3 Raymond R Tjandrawinata4 1Obstetric Gynecology Department, Faculty of Medicine, Diponegoro University, Semarang, Indonesia; 2Obstetric Gynecology Department, Dr. Kariadi Hospital, Semarang, Indonesia; 3Enviromental Health Department, Diponegoro University, Semarang, Indonesia; 4Research and Business Development, Dexa Laboratories of Biomolecular Science Research, Tangerang, IndonesiaCorrespondence: Syarief Thaufik Hidayat, Department of Obgyn, Faculty of Medicine, Diponegoro University, Kariadi Hospital Semarang, Central Java, Jalan dr. Sutomo No. 16, Randusari, Kecamatan Semarang Selatan, Kota Semarang, Semarang, 50244, Indonesia, Tel +62 812 2924 346, Email tofik.obg@gmail.comBackground: Polycystic ovary syndrome (PCOS) can lead to compensatory hyperinsulinemia with consequent metabolic abnormalities in women. In this study, DLBS3233 and Metformin were used to be tested. DLBS3233 itself is the new insulin-sensitizing drug, a combination-bioactive-fraction derived from two Indonesian herbals, Lagerstroemia speciosa and Cinnamomum burmannii. DLBS3233 alone and in combination with metformin were evaluated for efficacy and safety in insulin-resistant women with polycystic ovary syndrome (PCOS).Methods: A randomized, double-blind, 3-arm, double-dummy, non-inferiority, and also a controlled clinical study was conducted at the Dr. Kariadi Hospital, Indonesia, between October 2014 and February 2019. The study involved 60 female subjects (with 20 female subjects in each group) that had polycystic ovary syndrome (PCOS).Treatment I consists of one placebo capsule twice per day and one 100 mg DLBS3233 capsule once per day. Treatment II consists of one placebo caplet once per day and one 750 mg Metformin XR caplet twice per day. Treatment III consists of one 750 mg Metformin XR caplet twice per day and one 100 mg DLBS3233 capsule once per day.Results: In treatment I, the homeostatic model assessment for insulin resistance (HOMA-IR) levels were 3.55, 3.59, and 3.80 at pretest, 3 months, and 6 months after intervention, respectively. In treatment II, the HOMA-IR level were 4.00, 2.21, and 4.40 at pretest, 3 months, and 6 months after intervention respectively. In treatment III, the HOMA-IR levels were 3.30, 2.86, and 3.12 at pretest, 3 months, and 6 months after intervention, respectively. There was no apparent difference existed in the fasting plasma glucose (FPG), high-density lipoprotein (HDL), triglycerides, ferriman-gallwey scores (FGS), and safety assessment on vital signs and laboratory examinations (liver function and renal function) in all groups.Conclusion: Either DLBS3233 alone or the DLBS3233/Metformin combination showed no significant efficacy and did not negatively affect cardiovascular function, liver and kidney function in PCOS subjects.ClinicalTrials.gov Identifier: NCT01999686 Date: 3rd of December, 2013.Keywords: homeostatic model assessment for insulin resistance, metabolic parameters, DLBS3233, metformin, polycystic ovary syndrome